2011
DOI: 10.1088/0031-9155/56/14/003
|View full text |Cite
|
Sign up to set email alerts
|

Image quality assessment in digital mammography: part II. NPWE as a validated alternative for contrast detail analysis

Abstract: Assessment of image quality for digital x-ray mammography systems used in European screening programs relies mainly on contrast-detail CDMAM phantom scoring and requires the acquisition and analysis of many images in order to reduce variability in threshold detectability. Part II of this study proposes an alternative method based on the detectability index (d') calculated for a non-prewhitened model observer with an eye filter (NPWE). The detectability index was calculated from the normalized noise power spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 34 publications
3
59
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] The objectives of these studies are to (1) assist computer aided diagnosis systems in chest radiography and mammography, 1,2 (2) optimize dose, 7,12 (3) compare model results with conventional Fourier domain metrics, 3,6,10,11 and (4) evaluate the performance of digital mammography systems in the spatial 5 and Fourier domains. 8,9 Many of these investigations relied on simulated data, 4,6,7,[10][11][12] or a Fourier-based metric, 3,4,8,9 which requires assumptions that do not necessarily reflect actual digital x-ray systems. 6,10,11 Additionally, application of linear observer models to fluoroscopic and angiographic imaging systems has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The objectives of these studies are to (1) assist computer aided diagnosis systems in chest radiography and mammography, 1,2 (2) optimize dose, 7,12 (3) compare model results with conventional Fourier domain metrics, 3,6,10,11 and (4) evaluate the performance of digital mammography systems in the spatial 5 and Fourier domains. 8,9 Many of these investigations relied on simulated data, 4,6,7,[10][11][12] or a Fourier-based metric, 3,4,8,9 which requires assumptions that do not necessarily reflect actual digital x-ray systems. 6,10,11 Additionally, application of linear observer models to fluoroscopic and angiographic imaging systems has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of scatter in the observer model may be taken into account in two ways: (1) using the presampling MTF (including the detector and focal spot blurs) along to the absolute object contrast (signal difference ΔP out ) and NPS (both measured on the images with scatter) (equation (23a)) or (2) using the system MTF (MTF sys ) along to the normalized object contrast (ΔP out /P out ) and NNPS, all three measured with scatter (equation (23b)). Both methods have been used in the literature: Monnin et al (2011) used the presampling MTF, while Liu et al (2014) used generalized MTF and NNPS in their observer model. The latter study showed the equivalence of the two approaches.…”
Section: Image Quality and Detection: Neq And Contrast-detail Analysismentioning
confidence: 99%
“…Different degrees of sophistication are possible: mathematical objects versus irregular shapes, homogenous backgrounds versus clustered lumpy backgrounds and even patient images, the choice of eye filter, etc. In selected studies, a correlation between the results of mathematical observers and the more simple contrast detail data could be shown [51]. Detectability d' can be used across systems.…”
Section: The Often Forgotten Dose Related Factor: Diagnostic Image Qumentioning
confidence: 99%